The Challenge of Radicalization and Extremism Integrating Research on Education and Citizenship in the Context of Migration - Gutzwiller-Helfenfinger, Eveline; Abs, Hermann J.; Göbel, Kerstin (Brill, 2022)
This interdisciplinary volume on The Challenge of Radicalization and Extremism: Integrating Research on Education and Citizenship in the Context of Migration addresses the need for educational researchers to place their work in a broader social and political context by connecting it to the current and highly relevant issue of extremism and radicalization. It is just as important for researchers of extremism and radicalization to strengthen their conceptual links with educational fields, especially with education for democratic citizenship, as for researchers in education to get more familiar with issues of migration. This book meets a current shortage of research that addresses these issues across subjects and disciplines to inform both scientific and professional stakeholders in the educational and social sectors. The volume is divided into three parts. The first part, Foundations, provides fundamental research on radicalization and the rejection of democratic values. In the second part, Analysis of Preconditions within the Educational Context, key risk and protective factors against radicalization for young people are explored. Finally, the third part, Approaches for Prevention and Intervention, offers concrete suggestions for prevention and intervention methods within formal and informal educational contexts. The contributions show how new avenues for prevention can be explored through integrating citizenship education's twofold function to assimilate and to empower.